Overview of Types of Cord Blood Banks - Da, Pham Xuan; Ly, Bui Thi Kim; Van Kien, Vu; Thanh Chi, Hoang (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2025)
This study aims to analyze different models of cord blood banks (CBB) worldwide and in Vietnam. The research was conducted through reviews and analyses of PubMed literature, data from decrees and circulars of the Vietnamese government related to the activities of stem cell banks, and information from the official websites of blood banks in Vietnam and globally. The analysis results indicated five main models: public CBB, private CBB, mixed CBB, charitable family CBB, and family CBB that can be donated. The study also analyzed the administrative agency of CBBs worldwide and the standards that CBBs must meet to ensure quality, safety, and the rights of users and donors. In recent decades, the number of CBBs has increased significantly. Private CBBs have surpassed public CBBs, as public CBBs face numerous financial challenges. Furthermore, mixed CBB models, charitable family CBBs, and family direct donation CBBs have emerged as new and promising forms.